(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Shear thickening fluids STFs are a new kind of materials that consist of nano/micro particles that dispersed in another material such as polymer. In this review paper, the definition of this type of materials and the mechanism of its work are explained. In addition, the main factors that can effect on this behavior and their applications in different area from simple applications to complex applications are shown briefly